Editorial of Dossier “Alternative methods, consensus and the role of the victim in criminal procedure law”: Victim participation in the penal conflict solution - Enrique Letelier Loyola (Revista Brasileira de Direito Processual Penal)
The resurgence of the victim, as a topic of interest for criminological sciences and criminal law, has caused the need to question whether traditional criminal justice models are adequate to satisfy their interests, considering that it is a protagonist of the criminal conflict. Collecting some restorative experiences and with the support of the most modern victimology, the criminal justice systems stop focusing only on the punishment of the offender and open themselves to the adoption of restorative justice programs, which recognize in the victim a subject holder of the right to the repair of the damage.